Novel application of HS-GC-IMS with PCA for characteristic fingerprints and flavor compound variations in NFC Chinese bayberry (Myrica rubra) juice during storage. (15th September 2022) - Xuan, Xiaoting; Sun, Ruiyang; Zhang, Xiyue; Cui, Yan; Lin, Xudong; Sun, Yong; Deng, Wenyi; Liao, Xiaojun; Ling, Jiangang
Abstract: The flavor fingerprint of NFC Chinese bayberry (Myrica rubra) juice treated by high hydrostatic pressure (HHP) was developed, and the volatile flavor compound variations formed during storage at 4 °C for 28 days were investigated by headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) fingerprinting combined with principal component analysis (PCA). During the bayberry juice storage period, the HS-GC-IMS provided information on the characteristics and intensity of 52 volatile flavor compounds (ten terpenes, fifteen aldehydes, fourteen esters, nine alcohols, three ketones and one furan) and was used to observe the changes in flavor compounds in bayberry juice during storage. The results showed that the contents of (E)-2-hexenal, (Z)-3-hexen-1-ol, linalool and 6-methyl-5-hepten-2-one increased first with prolonged storage time. While the methyl caproate and methyl isobutyrate contents continued to decrease, the 3-pentanone, 2-methylbutanal and 2-methacrolein contents increased gradually. In addition, ethanol (note "alcohol") and ethyl acetate (note "overripe") were found to contribute to off-flavor accumulation. The visual plots for HS-GC-IMS and PCA had good consistency, and their combination was excellent for characterizing the aroma characteristics of bayberry juice from different storage periods. This work can provide useful knowledge for understanding the flavors of NFC Chinese bayberry during storage. Highlights: A rapid method for flavor analyzing of NFC Chinese bayberry juice during storage was created based on HS-GC-IMS. 52 volatile compounds were identified, mainly including trans -caryophyllene, limonene, alpha-terpinene, beta-ocimene and ethyl acetate. Ethanol and ethyl acetate might be responsible for the off-flavor accumulation.